Peroxidação lipídica e parâmetros bioquímicos do sangue total felino armazenado em bolsas plásticas contendo CPDA-1 e CPD/SAG-M - Bertoletti, Bianca (2011)
This study aimed to evaluate the influence of lipid peroxidation on decrease of erythrocyte viability in total blood of cats stored in plastic bags containing CPDA-1 (citrate phosphate dextrose adenine) and CPD / SAG-M (citrate, phosphate, dextrose, saline, adenine, glucose, mannitol) for 28 days. It was also analyzed the biochemical and hematological parameters of feline blood throughout the storage period. To this end, were used 12 cats, adult, healthy, male and female, mixed breed, weighing on average 3.5 ± 0.6 kg. The animals were randomly divided into two experimental groups, designated G1 and G2, which was collected on average 15 mL/kg of blood, and stored in bags for shipment of blood products. For the preservation of blood it was used to G1 and G2 CPDA-1 and CPD / SAG-M, respectively. The blood was kept under refrigeration (1-6 ° C) for 28 days and samples were taken for analysis weekly. These rates were evaluated for lipid peroxidation measured by TBARS (thiobarbituric acid reactive substances), erythrocytes peroxidation in vitro, concentrations of potassium (K +) , lactate, glucose and extracellular hemoglobin, erythrocyte count, hematocrit (Ht), hemoglobin (Hb) and total plasma protein (TPP) Through these evaluations it was found that the lactate, potassium and extracellular hemoglobin are effective parameters to evaluate the quality of stored blood to felines and the analysis of TBARS applies to prove the association of lipid peroxidation decreased the viability of blood, also for the felines. Moreover, CPD/SAG-M was more efficient than CPDA-1 in maintaining the viability of the feline blood after 14 days in a storage period of 28 days.